VERICIGUAT: MODERN THERAPY FOR THE TREATMENT OF CHRONIC HEART FAILURE - Bylica, Dominik; Kaźmierska, Anna; Szydłowski, Radosław; Bodera, Magdalena; Rozmus, Sonja (International Journal of Innovative Technologies in Social Science, 2026)
Vericiguat is the first oral soluble guanylate cyclase (sGC) stimulator developed to reduce the risk of cardiovascular death and heart failure–related hospitalizations in patients with chronic heart failure with reduced left ventricular ejection fraction (HFrEF). sGC dysfunction, resulting in impaired synthesis of cyclic guanosine monophosphate (cGMP), may play a keyrole in the pathophysiology of heart failure by affecting myocardial function, vascular tone, and peripheral tissue perfusion.Vericiguat exerts its therapeutic effect by enhancing intracellular cGMP levels, leading to improved cardiac function and vasodilation. Consequently, the drug represents a promising treatment option for patients with HFrEF, particularly those with recent decompensation, requiring intravenous diuretic therapy, or at high risk for rehospitalization due to disease exacerbation.Clinical efficacy of vericiguat was demonstrated in the VICTORIA trial, which enrolled 6,857 patients with HFrEF following recent decompensation. After a median follow-up of 10.8 months, treatment with vericiguat significantly reduced the risk of the composite endpoint of cardiovascular death or heart failure related hospitalization compared with placebo. Patients with more advanced disease also exhibited reductions in NT-proBNP levels, suggesting a potential biomarker of therapeutic response. Vericiguat is generally well tolerated. The most commonly reported adverse events are hypotension and syncope. The drug can be safely administered to patients with mild to moderate renal or hepatic impairment, although data in severe organ dysfunction are lacking. Dose adjustments are not required based on age or body weight. The introduction of vericiguat into the management of HFrEF represents a meaningful advancement in therapy. While the drug does not significantly extend overall survival, its use is associated with a substantial reduction in the risk of recurrent hospitalizations, which may have important clinical and prognostic implications in this patient population.